Rediseño de la planta de producción de pulpa de fruta para la empresa Agrofruit en la ciudad de Píllaro - Díaz Robayo, Jhonatan Alexander (2023)
Before redesigning a production plant, it is important to know its strengths and weaknesses through direct observation and interviews with the people directly involved in it. "AGROFRUIT PURAFRUTA" is a family microenterprise of Ecuadorian origin which is dedicated to the production of fruit pulp, it was born by inspiration of Eng. Luis Luzuriaga who had the vision to undertake in this field and generate sources of work in this parish, currently the company has a total of 6 full-time employees, including the head of production and the owner manager. This company has had a growth in demand, which is why it went from selling 250 kg per month to 3 tons of product per month in recent 10 years and their spaces are reduced. Knowing this problem, it is proposed to carry out a redesign of the production plant in a new and larger locality that truly ensures the correct flow of the product, reducing delays, using the help of AutoCad and SketchUp software, a new plant is designed that preserves the production process, previously calculating its capacity, once drawn and analyzed how these solutions improve the aforementioned problems, we proceeded to carry out the simulation of both the current production process and our value proposition in order to know how much time it was possible to reduce in the new production plant using the Bizagi Modeler software.